Poverty-Focused Social Accounting Matrices for Tanzania, 1998-2001 - International Food Policy Research Institute (International Food Policy Research Institute, 2003)
The 1998 to 2001 social accounting matrices for Tanzania incorporate the recently released input-output table (1992) and Labor Force (LFS) and Household Budget (HBS) surveys (both for 2000/01). The SAMs distinguish between 43 productive sectors (activities) and the 43 commodities that they produce. There are nine labor categories drawn from the LFS and disaggregated according to education and gender (including one category for child labor). The SAMs also include agricultural and non-agricultural capital and agricultural land. There are 12 household categories distinguished by (i) being urban or rural, (ii) being below, between or above the two national poverty lines, and (iii) the education level of the head of the household. These poverty-focused categories were chosen based on findings from the HBS. Other institutions contained in the SAMs include the rest of the world, the government, enterprises, and the savings-investment account.